Response of Leaf Skeletonizer, Eutectona machaeralis (Walker) (Lepidoptera : Pyralidae), on some Progeny of Teak Clones of Madhya Pradesh - Roychoudhury, N.; Chourasia, Manish; Jalil, Parvez; Joshi, K. C. (Indian Forester, 2009)
A study was made to measure the differences among the progeny of 12 Teak clones of Madhya Pradesh, viz. C-5, 6, 8, 11, 60, 72, BBC-23, 28, 44, BSC-28, CSC-9 and KEKC-7, for damage impact and feeding potentiality of the larvae of Eutectona machaeralis (Walker), in nursery and laboratory respectively. Based on the level of larval defoliation impact and leaf consumption, response of this pest exhibited that progeny of clone CSC-9 of Chhindwada Sillewani was least preferred followed by C-11 and C-8 of Seoni Kurai, whereas most preferred clonal progeny was KEKC-7 of Khandwa East Kalibheet followed by BSC-28 of Betul Sarni. The weight gained by larvae fed on leaves of least and most preferred clonal progenies were significantly (P<0.05) reduced and greater than those of others respectively. The leaf water content of clonal progeny showed a gradual increase in relation to leaf consumption. All the parameters included in the study showed positive and significant (P<0.05-P<0.01) correlation. The findings suggest that the variation in progeny of Teak clones may play a decisive role for differential reaction of this insect pest.